Dalia Mogahed expressing woman’s language features during her Islamic lecture Body Image: Reality and Standard - Budiwati, Tri Rina; Putri, Belia Ananda (Journal of Religion and Linguistics, 2024)
Differences between men's and women's language use are due to the structure of the language, social norms, or the people in society who use the language. Holmes also explained that standard speech forms usually refer to women and femininity. A theory mentioned a particular woman's speech pattern that suggested fragility, unsureness, and unimportance. This research aimed to investigate the features used by Dalia Mogahed in her Islamic lecture Body Image Reality and Standards to prove the theory. The research method in this study is categorized as qualitative research since the descriptive data in this study is presented in spoken or written words by people. The researcher found 6 out of 10 features used by Dalia; they are lexical hedges, tag questions, rising intonation, empty adjectives, intensifiers, and hypercorrect grammar. It can be concluded that women in majority prefer using feminine features to bargain the position in the society.